A Z‐Scheme Polyimide/AgBr@Ag Aerogel with Excellent Photocatalytic Performance for the Degradation of Oxytetracycline. Issue 3 (9th January 2019) - Zhao, Xinfu; Wang, Xinqiang; Zhang, Jian; Yi, Xibin
Abstract: A novel Z‐scheme polyimide (PI)/AgBr@Ag aerogel photocatalyst has been successfully synthesized by combining an in situ precipitation method and a supercritical drying method. The as‐prepared PI/AgBr@Ag‐50 (50 wt % AgBr@Ag in PI/AgBr@Ag) aerogel photocatalyst exhibited excellent photocatalytic activity for oxytetracycline degradation with a rate constant of 0.025 min −1, which was 6.9 and 2.6 times higher than that of the PI aerogel or the AgBr@Ag nanoparticles, respectively. More significantly, the PI/AgBr@Ag‐50 aerogel photocatalyst showed stable cycling, which could be attributed to the high mechanical strength and 3D network of the PI aerogel. The introduction of AgBr@Ag on PI with a heterojunction structure efficiently promoted the separation of electron–hole pairs by a Z‐scheme mechanism. The reduced metallic Ag nanoparticles were found to function as centers for the transfer of electrons from AgBr to PI. This work has revealed a new application for the aerogel PI/AgBr@Ag photocatalyst in environmental protection. Abstract : Two is better than one : AgBr@Ag nanoparticles were uniformly dispersed on a polyimide (PI) aerogel, and the resultant Z‐scheme PI/AgBr@Ag composite aerogel exhibited excellent photocatalytic activity for oxytetracycline (OTC) degradation under visible light, which can be attributed to the synergy between the AgBr@Ag plasmonic photocatalyst and the PI semiconductor photocatalyst (see figure).